A CONSTITUIÇÃO DO CAMPO ACADÊMICO DA POLÍTICA EDUCACIONAL NO BRASIL - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
This research aimed to analyze the constitution of the academic field of educational policy in Brazil. This analysis involved the investigation of processes that permeate the history of educational policy as a specific field as well as the identification of temporal boundaries in the constitution process of this field within the Brazilian context. The theoretical framework was based on Pierre Bourdieu’s contributions on the notion of field, authors who point out elements that mark the institutionalization of a particular field (GÓMEZ CAMPO; TENTI FANFANI, 1989; SUASNÁBAR; PALAMIDESSI, 2007), authors that ground the concept of educational policy and its study subjects (BALL, 1994; RIZVI; LINGARD, 2010; among others) as well as studies that discuss aspects of the history and the production of knowledge of the educational policy field (AZEVEDO; AGUIAR, 2001a, 2001b; SANTOS, A. L., 2009; among others). The research was of qualitative nature and characterized as documentary and bibliographic, involving a series of data collection, such as: newsletters and ANPEd conference proceedings; Capes and CNPq documents; curricula of Pedagogy undergraduate courses; records about the history of scientific associations (ANPEd, ANPAE); periodicals, conferences and specific research networks in the field; productions on and about the field of educational policy in Brazil and other countries. In addition to the documentary and bibliographical analysis, this research included an interview with two key-researchers from the academic field of educational policy. It argues that educational policy in Brazil emerges as a specific academic field, after the 1960s, having studies on school administration, educational administration and comparative education as its background. Although the 1960s can be considered the beginning of the emergence of the field over a number of aspects such as the creation of ANPAE, the implementation of Post-Graduation in Brazil, a more frequent use of the term ‘Educational policy(ies)’ in titles of Brazilian publications, an explicit milestone in the institutionalization process in this field, was the creation of GT 5 - State and Educational Policy within the scope of ANPEd (1986/1987). As a product of historical and social conditions, after the 1990s, the field gains more autonomy and legitimacy through the expansion of publications on educational policy; creation of disciplines on educational policy;creation of Post-Graduation research lines and groups; creation of specialized scientific journals; creation of research networks and holding specific scientific conferences related to educational policy. The current context indicates that, in Brazil, the academic field of educational policy is found in an expansion process and in search for consolidation. The research results indicate that it is a field still under construction, with several issues to be resolved towards its consolidation, such as: better definition of its study subjects (as it is characterized as an inclusive and comprehensive field), the expansion of theoretical frameworks for policy analysis, the concept of what educational policy is, the internationalization of educational policy studies, the expansion of the dialogue with political science, social science, economics, as well as the contributions that result from continuous development of social theory, in a broad sense.
The constitution of the academic field of educational policy in Brazil
Keywords: política educacional - Brasil; teoria dos campos; Pierre Bourdieu; educational policy - Brazil; Field theory; Pierre Bourdieu; CNPQ::CIENCIAS HUMANAS::EDUCACAO